2014
DOI: 10.1002/chir.22406
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticonvulsant Activity and Metabolism of 4‐chlor‐3‐methylphenoxyethylamine Derivatives of Trans‐2‐aminocyclohexan‐1‐ol

Abstract: In this study, we report the synthesis, spectral characterization, antiepileptic activity and biotransformation of three new, chiral, N-aminoalkyl derivatives of trans - 2 aminocyclohexan-1-ol: (R enantiomer), (S enantiomer) and (racemate). Antiepileptic activity of the titled compounds was studied using MES and scMet. Moreover, in this study, the biotransformation of , and in microbial model (Cunninghamella), liver microsomal assay as well as in silico studies (MetaSite) was evaluated. Studies have indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
4
8
0
Order By: Relevance
“…Moreover, our in silico data coincide with in vitro experiments, as three MetaSite metabolites of PZ‐1150 matched compounds identified in microsomal samples. Similar observations were made when the metabolism of some trans ‐2‐aminocyclohexan‐1‐ol derivatives with the use of C. blakesleeana , RLMs, and MetaSite was investigated . Metasite predicted two metabolites, which were also identified using the Cunninghamella model and RLMs .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Moreover, our in silico data coincide with in vitro experiments, as three MetaSite metabolites of PZ‐1150 matched compounds identified in microsomal samples. Similar observations were made when the metabolism of some trans ‐2‐aminocyclohexan‐1‐ol derivatives with the use of C. blakesleeana , RLMs, and MetaSite was investigated . Metasite predicted two metabolites, which were also identified using the Cunninghamella model and RLMs .…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with previous reports comparing xenobiotics biotransformation by Cunninghamella spp. and microsomes, which indicated that the generated metabolites are comparable . Moreover, our in silico data coincide with in vitro experiments, as three MetaSite metabolites of PZ‐1150 matched compounds identified in microsomal samples.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations